Analisis Pengaruh Faktor-Faktor Wajib Pajak Kendaraan Bermotor di Provinsi Banten Tahun 2020 - Esa Kurnia Ramadhan (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study is to analyze the compliance factors of automobile taxpayers. Understand Banten's taxation, tax penalties and quality of public services in 2020. This study uses a quantitative description with an unlikely sampling method that uses a saturated sampling technique where sampling is used when all members of the population are considered. .. The population surveyed was 100 people who own cars in Banten. The data analysis method used the views 10 application. Analysis includes testing of research tools, including validation tests. The classic acceptance test consists of a normality test, a non-uniform variance test, and a multiple correlation test. Hypothesis tests include f-test, t-test, and R2 test (coefficient of determination). The results showed that understanding taxation and the quality of public services did not affect taxpayer compliance, but tax sanctions had a positive impact on taxpayer compliance